2006
DOI: 10.1063/1.2236103
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy energy of antiferromagnetic L1-type equiatomic Mn alloys

Abstract: The theoretical calculations of magnetic anisotropy energy (MAE) for antiferromagnetic L10-type MnTM [transition metal (TM)=Ni, Pd, Pt, Rh, and Ir] alloys were carried out on the basis of the local spin-density approximation using linear muffin-tin orbital method with atomic sphere approximation including the spin-orbit interaction. It has been demonstrated that the magnitude of the MAE for L10-type MnIr alloy is highest, −20.77×106J∕m3, and the negative sign of the MAE is consistent with the reported spin str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 28 publications
7
34
0
Order By: Relevance
“…Furthermore, Mn is a relatively inexpensive metal, which is of utmost importance in light of the current tight supply and high cost of the rare-earth elements that are used in current advanced magnets [1]. Unfortunately, most manganese compounds are antiferromagnetic, which is typical for compounds formed from elements in the middle of the 3d series [2,3]. This situation precludes the use of Mn in many applications that require ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Mn is a relatively inexpensive metal, which is of utmost importance in light of the current tight supply and high cost of the rare-earth elements that are used in current advanced magnets [1]. Unfortunately, most manganese compounds are antiferromagnetic, which is typical for compounds formed from elements in the middle of the 3d series [2,3]. This situation precludes the use of Mn in many applications that require ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…For example, MnPt alloys with the tetragonal L1 0 structure are antiferromagnetic with high Néel temperatures resulting from antiparallel coupling between adjacent Mn atom located in (001)-planes [4]. Similarly, MnRh, MnPd, MnIr and MnNi alloys are also antiferromagnetic [2]. It is important to understand how the magnetic properties of Mn-based compounds depend upon chemical and structural details.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the anisotropy, Umetsu et al 8 calculated the magnetic anisotropy energy (MAE) of L1 0 -type MnTM (TM=Ni, Pd, Pt, Rh and Ir) compounds and revealed that MnIr had the highest MAE with a value of -7.05 meV/unit cell. Furthermore, a giant second order magnetic anisotropy for L1 2 IrMn 3 was reported, leading to energy barriers of the order of K eff = 10.4 meV/unit cell for rotation of the T 1 ground state spin-structure around the (111) axis.…”
Section: Introductionmentioning
confidence: 99%
“…An example of an antiferromagnet with very strong easy-plane anisotropy is MnIr ͑K 1 = −21 MJ/ m 3 ͒. 17 An experimental approach would be to start from an easyplane magnet and to use mechanical alloying ͑ball milling͒ to create oblique nanoscale interfaces. For example, Sm 2 Co 14 B, which has a room-temperature magnetization of 1.51 T and an anisotropy of −12.0 MJ/ m 3 , 18 compared to +4.9 T for Nd 2 Fe 14 B, would then yield a fairly hard material.…”
Section: Semihard Phasesmentioning
confidence: 99%